Bakayat: Endangered Traditions of Oral Literature in West Sumatera - Djalius, Yusmarni (Vivid: Journal of Language and Literature, 2023)
This is historical research on traditional oral literature, bakayat, performed in West Sumatra, Indonesia. As preliminary research, it primarily aimed to document the performance and collect its scarcely written sources. Data and sources were collected through observation, interview, and documentation methods. Descriptions of the performance or narrative, narrator or storyteller, text, and context are provided in this essay to introduce bakayat as a Minangkabau art and literature and to place it in a larger literary context.The data were collected by observing and recording bakayat in its actual performance setting, obtaining documents and archives, and interviewing its storytellers. The study found that bakayat is seriously endangered. Used to be one of the most attended performances in the area, bakayat is no longer appealing to young audiences. The sustainability and continuity of bakavat as a local tradition are at stake. Therefore, serious measures must be formulated and taken by the government, local adat dignitaries, and other cultural stakeholders to promote this unique tradition and encourage the young audience to learn and preserve bakayat.